Kajian Hukum Islam atas Sistem Tebasan dalam Transaksi Jual Beli Batu Gunung - Haidar Hubbanlillah, Muhammad; Saputra, Wahyu (Jurnal Antologi Hukum, 2025)
Buying and selling is a common practice in society, including in Arjosari Village, Arjosari District, Pacitan Regency. One form found in this community is the sale of land containing mountain stones through the tebasan system, where the price is determined by estimation without precise measurement. This study aims to analyze the validity of the contract (akad) and the price determination in this practice from the perspective of Islamic law. This research employs a qualitative field approach, with data collected through interviews, observations, and documentation. The findings show that the sale and purchase contract using the tebasan system cannot be considered valid under Islamic law. Although the ijab qabul is fulfilled based on mutual consent, the object of sale involves uncertainty (gharar) due to the absence of clear standards regarding the quantity and volume of stones. Moreover, the method of price determination is not fully aligned with Islamic legal principles, as it creates the potential for harm to one party. Buyers may suffer losses if the stones are fewer than estimated, while sellers may be disadvantaged if buyers gain excessive profit. In conclusion, the tebasan system in the sale of mountain stones raises legal issues in Islamic law, particularly concerning contractual certainty and fairness in pricing.